Novel Angiotensin-Converting Enzyme-Inhibitory Peptides From Fermented Bovine Milk Started by Lactobacillus helveticus KLDS.31 and Lactobacillus casei KLDS.105: Purification, Identification, and Interaction Mechanisms - Li, Jiaqi; Zhao, Jiajia; Wang, Xindi; Qayum, Abdul; Hussain, Muhammad Altaf; Liang, Guizhao; Hou, Juncai; Jiang, Zhanmei; Li, Aili (Frontiers in Microbiology, 2019)
Fermented milks with strong angiotensin-I-converting enzyme (ACE) inhibitory activity were obtained by culturing with Lactobacillus helveticus KLDS.31 and Lactobacillus casei KLDS.105 with a fermentation and storage temperature of 37 °C. Ultrafiltration fractions with molecular weight less than 3 kDa in fermented milk whey exhibited the strongest inhibitory activity. Correspondingly, a gastrointestinal digestion experiment showed retention of the bioactivity of these fractions with pepsin and trypsin treatment. Four ACE inhibitory peptides from fermented milk were isolated, purified by a two-step reverse chromatography, and sequenced. Furthermore, the interaction mechanisms between ACE and four isolated peptides were investigated by molecular docking method and the Independent Gradient Model. Experimental determination of IC50 was done to verify theoretical results. The inhibitory peptide interacted with ACE as follows: Lys-Pro-Ala-Gly-Asp-Phe > Lys-Ala-Ala-Leu-Ser-Gly-Met > Lys-Lys-Ala-Ala-Met-Ala-Met > Leu-Asp-His-Val-Pro-Gly-Gly-Ala-Arg.